PENGURANGAN BULLWHIP EFFECT DALAM RANTAI PASOK DENGAN METODE COLLABORATIVE PLANNING, FORECASTING AND REPLENISHMENT (CPFR - Atika Ayu Derari; Andhika Mayasari; Nur Muflihah; Sumarsono (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2022)
Abstract The supply chain is a network system of several interconnected organizations with the same goal of distributing production goods and services to their customers. PT. Samudera Gemilang Plastindo (PT SGP) is a company engaged in the processing of plastic seeds, one of the products produced is HDPE T-Shirt Bag. The supply chain system studied at PT. SGP consists of a Manufacturing (Vendor) and 3 Sales Offices (SIM Jember, Depo Bali and 3S Bogor) because they often experience inaccuracies in forecasting data which causes the Bullwhip Effect phenomenon or information distortion to meet customer needs. Initially, forecasting was carried out at each level of the supply chain using different forecasting methods and inventory planning was carried out separately and not coordinated with each other. Therefore, we need an equation in choosing a forecasting method to synchronize the forecasting results and the implementation of production in each supply chain actor. This study uses the Collaborative Planning and Replenishment (CPFR) method, which is a method that combines production planning, forecasting and inventory control. The results of testing several forecasting methods, the method chosen is the Winter's Method because it has the smallest error value. Inventory control is done by calculating the optimal lot, namely Economic Order Quantity (EOQ). The results of demand forecasting and determining the optimal lot are used to calculate the value of the Bullwhip Effect that occurs after the use of the CPFR approach in the supply chain at the vendor level (PT SGP) has changed from 1.285 to 0.729, while in the three Sales Offices there has been a change from 1.321 to 0.528 in SIM Jember sales office, 1.266 to 0.602 at Bali Depo sales office, 1.377 to 0.412 at 3S Bogor sales office.